Emerging Role of Mechanical Forces in Cell Fate Acquisition - Yanina Alvarez; Michael Smutny (Frontiers in Cell and Developmental Biology, 2022)
Mechanical forces are now recognized as key cellular effectors that together with genetic and cellular signals physically shape and pattern tissues and organs during development. Increasing efforts are aimed toward understanding the less explored role of mechanical forces in controlling cell fate decisions in embryonic development. Here we discuss recent examples of how differential forces feedback into cell fate specification and tissue patterning. In particular, we focus on the role of actomyosin-contractile force generation and transduction in affecting tissue morphogenesis and cell fate regulation in the embryo.